Deal or No Deal : Strictly Business for China in Kenya? - Sanghi, Apurva; Johnson, Dylan (World Bank, Washington, DC, 2016)
Existing work on China's economic influence in Africa refers to Africa in broad terms, thereby generalizing the results to an extent that is unhelpful for policy-makers in a specific country. Moreover, the emphasis is on oil exporters. This paper remedies this by focusing on a single, oil-importing country: Kenya. The paper examines China's economic presence in Kenya and some of the popular myths surrounding Chinese economic activity. The first myth is that Chinese companies do not employ local workers. In fact, 78 percent of full-time and 95 percent of part-time employees in Chinese companies are locals. Second, although China represents a large potential market for local exporters, the study finds that China has a better chance of expanding its exports to Kenya than Kenya does to China based on existing specializations. This may change with recent oil discoveries in Kenya, increasing the space for Kenyan exports to China, as well as from China's shift to a consumption-driven economy which will increase demand for services, a growing strength of Kenya's economy (World Bank Country Economic Memorandum 2016). The paper emphasizes that Kenyan policy makers should be less concerned about bilateral trade imbalances and worry about Kenya's overall trade balance. However, the Standard Gauge Railway and Thika superhighway experiences suggest that Chinese firms offer relatively few technology transfer or supplier opportunities for local firms and academia. Third, the popular focus of Chinese competition is on the impact on well-organized Kenyan producers and not on consumers, thereby underestimating the benefits Kenyan consumer derive from the availability of more affordable Chinese goods. The paper concludes with policy directions for improving export competitiveness and transparency in infrastructure projects, and local content.